2016
DOI: 10.1021/acsmacrolett.5b00823
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Intractable No More: In Vivo Incorporation of “Click”-Ready Fatty Acids into Poly-[(R)-3-hydroxyalkanoates] in Escherichia coli

Abstract: Poly-[(R)-3-hydroxyalkanoate] biopolymers, or PHAs, are biocompatible and biodegradable polyesters that can be produced by diverse microbial strains. PHA polymers have found widespread uses in applications ranging from sustainable replacements of nonbiodegradable bulk-commodity plastics to biomaterials. However, further expansion into other markets and industries has generally been limited by the inability to chemically modify these polymers. Recently, our lab engineered E. coli LSBJ, a microbial strain able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Additionally, during the review process of this paper, Nomura et al reported an in vivo synthesis of clickable PHA polymers utilizing ω-azido fatty acids as the feedstocks. 62 Since HHxCoA could be metabolically generated from 3-( R )-hydroxy-5-hexynoic acid 63 and exhibits high reactivity toward PhaC Cs (22% activity of HBCoA), it is currently used as a probe to investigate the formation of PHA granules.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, during the review process of this paper, Nomura et al reported an in vivo synthesis of clickable PHA polymers utilizing ω-azido fatty acids as the feedstocks. 62 Since HHxCoA could be metabolically generated from 3-( R )-hydroxy-5-hexynoic acid 63 and exhibits high reactivity toward PhaC Cs (22% activity of HBCoA), it is currently used as a probe to investigate the formation of PHA granules.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were concentrated to relative dryness using a rotary evaporator, and redissolved in 1 mL chloroform. Crude polymers were purified by non-solvent precipitation in cold methanol as described previously (Pinto et al 2016), with several modifications. Briefly, dissolved samples were added dropwise to 10 mL of ice-cold methanol (4 °C) with rapid stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The weight average (M w ) and number average (M n ) molecular weights for each sample were determined by gel permeation chromatography (GPC) as described previously (Pinto et al 2016). Briefly, PHA solutions of approximately 1.0 g L −1 were prepared by dissolution in chloroform and passed through a syringe filter (0.45 μm PTFE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, recent protein engineering of the synthase or structural proteins demonstrated that various functional proteins can be attached to the PHA granule surface and stably maintained outside the cell as bio‐beads. Therefore, using genetically engineered PHA synthase could aid in the introduction of specific functionalities into PHA granules, which will further broaden its applications in advanced delivery systems …”
Section: Pha‐based Nanovehicles As Therapeutic Delivery Carriermentioning
confidence: 99%